Impact of Exchange Rate Volatility on Sri Lankan Bilateral Demand of Imports - Jayasinghe, J.A.K.S.; Weerasinghe, W. D. J. D. (Department of Finance, Faculty of Commerce and Management Studies, University of Kelaniya Sri Lanka, 2020)
Purpose - The value and importance of imports of the Sri Lankan economy has been increasing according to statistical patterns of Sri Lanka. The exchange rate volatility is one major factor that has an impact on the demand for imports in a country. This research has been carried out to identify the impact of exchange rate volatility (long-run influence) on Sri Lankan bilateral demand of imports. Design/Methodology/Approach- Monthly data has been used for the study for the period of 2013 to 2019. GARCH and standard deviation techniques were used to measure the exchange rate volatility of USD/LKR exchange rate and exporter currency exchange rates. The autoregression distributions lag (ARDL) bound test approach was the model that has been used to estimate the long-run effect of the volatility clustering. Findings - According to the findings of China, Indian, Japan, the UK, Singapore, Hong Kong, and the USA country models, the error terms are highly significant at 5% and 10% levels. Thus, it indicates that there is a long-run impact from exchange rate volatility on-demand on Sri Lankan bilateral imports. Contribution - The study fulfils the existing research gap in exchange rate volatility and Bilateral demand of imports of Sri Lanka. The findings of this study will help the country to plan their bilateral demand of imports when exchange rate volatility exists and enables future researchers to conduct studies related to this area.
Keywords: ARDL approach, Bilateral imports, Exchange rate, GARCH effect, Volatility clustering